Reformation in the context of world Christianity : theological, political and social interactions between Africa, Asia, the Americas and Europe - Ludwig, Frieder; Richebächer, Wilhelm; Laaser, Mirjam; Ekué, Amélé; Pong, Pui-Yee (Studien zur Aussereuropäischen Christentumsgeschichte (Asien, Afrika, Lateinamerika) /Studies in the History of Christianity in the Non-Western World (Asia, Africa, Latin America), 2019)
The 500th anniversary of Luther's 95 theses in 2017 was the first such commemoration in which the global dimensions of the reformation were highlighted. This volume - the outcome of a conference held at the Fachhochschule für Interkulturelle Theologie Hermannsburg in June 2016 - reflects theological, political and social interactions between Africa, Asia, the Americas and Europe and explores new ways in which "Reformation" and "World Christianity" can be connected. It also analyzes negotiation processes in selected countries, focussing especially on the role of churches in social development, transformation processes and international discourses. --